A prospective open‐label, multicentre study evaluating a non‐cross‐linked hyaluronic acid based soft‐tissue filler in the correction of lateral canthal and perioral lines. (24th September 2021) - Sulovsky, Monika; Müller, Daniel; Prinz, Valentina; Moellhoff, Nicholas; Cajkovsky, Mia; Duschek, Nikolaus; Frank, Konstantin
Abstract: Objective: The aim of this investigation was to assess the effectiveness of a non‐cross‐linked hyaluronic acid based soft‐tissue filler in the correction of lateral canthal lines and periorbital lines. Material and methods: A total of 59 female Caucasian patients with a mean age of 52.6 ± 9.0 years were enrolled in this prospective open‐label, multicentre study and received intradermal injections of a soft‐tissue filler at baseline, after 3 and 6 weeks. Aesthetic improvement and patient satisfaction, skin hydration, skin firmness and skin elasticity, as well as adverse events were assessed at 3, 6, 8, 12 and 16 weeks. Results: At baseline, the lateral canthal skin firmness was 0.206 ± 0.07 mm and increased after 8 weeks to 0.087 ± 0.08 mm with p < 0.001, while the perioral skin firmness was 0.205 ± 0.09 mm and increased after 8 weeks to 0.116 ± 0.08 mm with p < 0.001. Increases in skin hydration were observed after 8 weeks in both areas, however, did not reach statistical significance at any point. At week 8, 12 and 16 a majority (93.1%, 91.1% and 73.7% respectively) of the patients stated that they were 'satisfied' or 'very satisfied' with the treatment. Conclusion: Overall, the skin firmness and skin visco‐elasticity showed significant increases in the lateral canthal and perioral region. Moreover, albeit not statistically significant, skin hydration increased in both areas after 8 weeks. The procedure has been shown to be safe and satisfactory for the treated patients; however, emergence of oral herpes should be added to the safety profile of intradermally applied hyaluronic acid treatments.